General, Applied and Systems Toxicology 2009
DOI: 10.1002/9780470744307.gat144
|View full text |Cite
|
Sign up to set email alerts
|

Organic Solvents

Abstract: This chapter describes the exposure, absorption, metabolism and toxic effects, particularly effects to the nervous system, of organic solvents. Since both occupational and domestic exposure is usually to mixtures of individual solvents rather than to single compounds, the metabolic interaction of solvents is addressed, as well as toxic effects of mixtures. Organic solvents have many clinical effects in common, but some solvents have individual effects, for example, the polyneuropathy induced by n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 183 publications
0
1
0
Order By: Relevance
“…8,17,18 Solvents have been linked to neurobehavioral changes, short-term memory impairment and loss of psychomotor functions. 18 There is limited research on the effects of organic solvents on the immune system however a recent meta-analysis concluded that such exposure is significantly associated with an increased risk of autoimmune diseases, including MS, primary systemic vasculitis, and systemic sclerosis. 17 Therefore, organic solvents likely exert their toxic effects through molecular mechanisms involving the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…8,17,18 Solvents have been linked to neurobehavioral changes, short-term memory impairment and loss of psychomotor functions. 18 There is limited research on the effects of organic solvents on the immune system however a recent meta-analysis concluded that such exposure is significantly associated with an increased risk of autoimmune diseases, including MS, primary systemic vasculitis, and systemic sclerosis. 17 Therefore, organic solvents likely exert their toxic effects through molecular mechanisms involving the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…In no-predisposed animals, pretreatment with inorganic mercury can exacerbate autoimmune disease even prior to disease induction (11). Moreover, exposure to OSs such as toluene or xylene has been postulated to affect MS risk through altered immune function or neurotoxicity (12,13).Although it is believed that MS is multifactorial in etiology, finite studies have examined the role of…”
mentioning
confidence: 99%